The output value-added tax implications for South African vendors of purchases made by means of loyalty points - Maluleke, Mikateko (My University, 2018)
The use of loyalty programmes has in recent years become popular in South Africa. There has, however, been only one public document that has been issued by the South African Revenue Service (‘SARS’) which discusses the Value-Added Tax (‘VAT’) treatment of loyalty programmes that was published in August 2014.1 Only one ruling has been issued to particular taxpayer on this subject.2 Therefore, there is little guidance on this subject in South Africa. This report seeks to examine the VAT implications (specifically the VAT output implications) of loyalty programmes for VAT vendors who participate in South Africa’s loyalty programmes. The report will explore some of the types of available loyalty programmes and explore the definition of ‘consideration’ as well as how other jurisdictions treat VAT output on loyalty programmes
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfillment of the requirements for the degree of Master of Commerce in the field of Taxation 2018